Peningkatan Proses dan Hasil Belajar IPAS Menggunakan Metode Pembelajaran Game Based Learning dengan Educaplay di Kelas IV SDN 127/II Sungai Arang - Mawarni, Ayu; Sundahry, Sundahry; Putra, Randi Eka (CV. Master Literasi Indonesia, 2025)
Based on the results of observations, the researcher found that 7 (47%) out of 15 students from the IV grade at SDN 127/II Sungai Arang had not yet reached the criteria called Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) score of 75. The purpose of this study was to describe the improvement in both the learning process and cognitive learning outcomes through the use of Game Based Learning with Educaplay in the IV grade at SDN 127/II Sungai Arang. This study employed a design called Penelitian Tindakan Kelas (PTK) conducted in two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subjects of this study were 15 students from the IV grade. Data collection techniques included observation, learning outcome tests, and documentation. Data collection instruments comprised teacher and student observation sheets, as well as learning outcome test items used to implement the Game Based Learning method with Educaplay. The results showed that the use of Game Based Learning with Educaplay improved student’s understanding of the material. This was evidenced by the increase in teacher observation scores from 74% in cycle I to 88% in cycle II, categorized as good. The student’s learning process scores also improved from 33% (very poor) in cycle I to 77% (good) in cycle II. Furthermore, student’s cognitive learning outcomes in the IPAS subject increased from 60% (not yet achieved) in cycle I to 80% (achieved) in cycle II.